Optimization of Hot Water Treatment for Sprout and Spoilage Inhibition of Cured Sweet Potato. Issue 1 (7th August 2012) - Sheibani, Ershad; Kim, TaeJo; Wang, Dja Shin; Silva, Juan L.; Arancibia, Ramon; Matta, Frank B.; Picha, David
Abstract The effect of hot water treatment on inhibition of sprouting and spoilage of cured sweet potatoes was investigated. The surface plot showed that as processing temperature and time of hot water treatment increased, spoilage increased until treated sweet potatoes showed 100% spoilage. The contour plot indicated that regardless of processing times (6–34 min), minimal sprouting (20%) was observed between 55 and 62C. Hot water treatment below 50C increased sprouting up to 100%. The overlapped contour plot indicated that hot water treatment at 53–56C for less than 10 min minimized spoilage (0–20%) and sprouting (30–50%) of cured sweet potatoes. Untreated sweet potatoes (control) showed 20% and 60% on spoilage and sprouting, respectively. High‐temperature treatment (70 and 74C) resulted in maltose formation in cured sweet potato. This study showed that simple hot water treatment proved successful in arriving at optima to reduce spoilage and sprouting. Practical Application As nonchemical methods, simple hot water treatment on cured sweet potato could minimize sprouting and spoilage with acceptable quality during storage.